Using time use diaries to assess physical activity and sedentary behavior in jail populations - Ricky Camplain; Sara Shuman; Adrienne Alonso; Elizabeth Schmitter; Javier Lopez; Amy Gelatt; Rebecca Annorbah; Isabel Fangman; Morgan Occhino; Brooke de Heer; Dirk de Heer; Meredith Brown; et al. (BMC Public Health)
Abstract Background People incarcerated have limited access to physical activity and there are challenges to accurately measure their physical activity in jail settings. We aimed to (1) determine the feasibility of time use diaries to measure physical activity and sedentary time among people incarcerated in jail and (2) estimate time spent in physical activity and sedentary behaviors, overall and by gender and job assignment. Methods In July 2023, we recruited women and men from two housing units at Yavapai County Detention Facility, a county jail in Camp Verde, Arizona. Participants were asked to complete a four-day time use diary, documenting activities in 10-minute increments. Participants provided feedback about the diary during listening sessions after the four-day period. Feasibility was measured as the proportion of people recruited who participated and the proportion of completed and returned diaries. Activities documented in the diaries were linked to the Compendium of Physical Activities to determine intensity and duration of physical activity and sedentary behavior. Average daily time spent in physical activity and sedentary behavior was calculated for each participant. Results Of the 24 women and 41 men recruited, 24 (100%) women and 40 (97.5%) men agreed to participate in the study. All diaries were returned. Most (82.8%) participants completed all four days in the diary. Participants were enthusiastic about filling out the diaries because they helped pass the time and felt the work would further knowledge and wellbeing in jails. Participants made concrete recommendations including altering the diary format to allow for additional detail about their time in jail. Participants spent on average 571 minutes sedentary, 79 minutes in light activity, and 60 minutes in moderate activity per day. Women spent 66 more minutes per day engaged in light activities compared to men. Women with job assignments spent 179 less minutes in sedentary behavior and 245 more minutes in moderate activity compared to women who did not have a job assignment. Conclusions Time use diaries are a feasible and appropriate way to measure physical activity and sedentary behavior among people incarcerated in jail.